Basal nitric oxide activity is an independent determinant of arteriolar structure in the human retinal circulation - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Schneider, Markus; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2011)
Experimental data indicate that nitric oxide might play a role in structure and remodeling of peripheral small arteries and arterioles. We hypothesized that retinal arteriolar structure is modulated by basal nitric oxide activity.The study cohort comprised 97 male untreated patients with normal and elevated blood pressure but without clinical evidence for cardiovascular disease. The changes of retinal capillary blood flow (RCF) to nitric oxide synthase inhibitor N-monomethyl-L-arginine (L-NMMA), that reflects basal nitric oxide activity of retinal vasculature, and to flicker light, that in part nitric oxide dependently provokes retinal vasodilatation, and parameters of retinal arteriolar structure, for example wall-to-lumen ratio (WLR), were assessed noninvasively and in vivo by scanning laser Doppler flowmetry.Participants were stratified according to the median WLR of retinal arterioles into two groups. In the group with WLR above the median RCF in response to infusion of L-NMMA decreased to a smaller extent (-3.82 ± 26 vs. -26.0 ± 45 arbitrary units and -0.83 ± 8.4 vs. -5.88 ± 11%, P = 0.004 and P = 0.015; respectively), whereas RCF in response to flicker light did not differ significantly compared to the counter group (22.2 ± 56 vs. 39.8 ± 51 arbitrary units and 7.42 ± 15 vs. 11.9 ± 14%, P = 0.112 and P = 0.149). In the whole study cohort WLR of retinal arterioles was related with the decrease of RCF to L-NMMA infusion [when expressed in absolute terms (r = 0.252, P = 0.013) and in percentage change (r = 0.213, P = 0.036)] and inversely related with the change of RCF to flicker light [when expressed in absolute terms (r = -0.203, P = 0.048) but not clearly when expressed in percentage change (r = -0.161, P = 0.120)]. Adjustment for major cardiovascular risk factors and changes of systemic hemodynamics in response to L-NMMA infusion revealed an independent relationship between WLR of retinal arterioles and percentage change of RCF to L-NMMA infusion (ß = 0.300, P = 0.007).Basal nitric oxide activity emerged as an independent determinant of arteriolar remodeling in the human retinal circulation in vivo.
EVALuna2:3475